Áreas de preservação permanente de topos: das alterações na legislação brasileira às suas diferentes interpretações - Amanda Machado de Almeida; Eduardo Vedor de Paula (Confins)
The Law of Protection Native Vegetation (Brazilian Forest Code) defines the norms, parameters and limits of the Permanent Preservation Areas (PPAs) and Legal Reserve (LR). Permanent Preservation Areas (PPAs) it has developed environmental functions such as soil protection and water conservation, that prevent the acceleration of erosion and silting processes, a problem that affects Antonina Bay, located in Paraná state coast. The PPAs included the categories of hilltops, hills, mountains, mountain systems and ridges in Law of number 4.771 in 1965. However, the PPAs had their delimitation rules defined by CONAMA Resolution 004/85, which repealed by Resolution 303/02. The last version of the legislation (12.651/12), in Article 4º, section IX, changed the category of hilltops PPAs, with the exclusion the ridges and changed the limits of hilltops, hills, mountains and mountain systems. Besides this, the Brazilian Forest Code is subjective, because the text can have three interpretations for concept of the base of terrain elevation for geomorphological features mentioned above. In this context, the present paper aims to carry out an evaluation of the modifications in the PPAs of hilltops between the previous and current legislation, as well as to compare the three interpretations of terrain elevation present in the current legislation. The study area was the Sacred River Basin (Morretes/PR), drainage area of Antonina Bay. With the application of the legislation current, the PPAs of hilltops reduced by 21% in relation to Law 4.771/65. Among the three interpretations of Law 12.651/12, there was a difference of more than 96% of the legally preserved area. Therefore, it is necessary to discuss the current legislation subjectivity, because the saddle point adoption as an elevation base may imply the occupation expansion of the areas susceptible to sediment production and consequently aggravate the sedimentation process of the studied basin.